Optimization of Hunhe waterfront parks in Shenyang based on Attention Restoration Theory - Wang, Yifei; Zhai, Jingmei; Zhuo, Jian (Frontiers in Public Health, 2025)
IntroductionRapid urbanization and increasing environmental pressures have intensified public health challenges, making the restorative potential of urban blue–green spaces a growing concern. Urban waterfront parks, as critical ecological and social infrastructures, play a significant role in promoting psychological recovery and physiological well-being. This study investigates how the spatial attributes and behavioral patterns of waterfront parks jointly shape restorative mechanisms, and how differentiated spatial optimization strategies can be proposed accordingly.MethodsSeven representative waterfront parks along the Hun River in Shenyang, China, were examined. Drawing upon Attention Restoration Theory, the study integrates objective spatial indicators and subjective perception data to construct a multi-dimensional evaluation framework. Methods including spatial analysis, questionnaire surveys, and multivariate statistical modeling were employed to identify the underlying mechanisms linking environmental qualities, user behaviors, and health restoration effects.ResultsThe findings reveal a multi-level interaction between spatial configuration, environmental perception, and behavioral participation in shaping restorative experiences. Different parks demonstrate distinct restorative orientations—socially interactive, psychologically reflective, and physiologically restorative—corresponding to variations in spatial form and user engagement. These results underscore that health restoration emerges not from single spatial elements, but from the synergistic relationship between environmental structure, sensory stimuli, and behavioral adaptability.DiscussionThe study establishes an integrated theoretical and analytical framework for assessing and enhancing the restorative potential of urban waterfront parks. It offers both conceptual insights and practical guidance for health-oriented spatial planning, contributing to the creation of adaptive, resilient, and human-centered public spaces in high-density urban environments.